Acute toxic and hepatopancreas syndrome caused by Chlopyrifos ethyl to black tiger shrimp (Penaeus monodon) and white shimp (Litopenaeus vannamei) in Mekong River Delta of Vietnam - Son, N. H.; Viet, T. Q.; Oanh, D. H.; Chi, D. P.; Huong, B. L.; Manh, N. H. (International Journal of Agricultural Technology, 2015)
Acute toxicity (96h) and chronic toxic (60 days early life stage) tests were conducted in laboratory to determind the LC50 and hepatopancreas syndrome of liver and gill of Chlopyrifos ethyl, an organophosphorus pesticide commonly used in Vietnam, to two major brackish water shrimps Penaeus monodon and Litopenaeus vannamei of Mekong River Delta to ensure the relevant of Chlopyrifos ethyl use with early motality symptom (EMS) of shrimps in Asia countries and the safety standard for water environment. The results indicate that the acute median lethal concentration (LC50) of Chlopyrifos ethyl to adults of Penaeus monodon and Litopenaeus vannamei, young age of Litopenaeus vannamei and Penaeus monodon is 0.1412; 0.1197; 0.0042 and 0.0041 mgl-1respectively. It means adults of both shrimps are more tolerent to Chlopyrifos ethyl than young ones (about 30 times) while the difference of tolerent between to tested species are not clearly recognized. Surgical histopathological assessment of hepatopancreassyndrome necrotizing pancreatitis in Chlorpyrifos ethyl showed exposure at low concentrations, shrimp in hepatopancreas samples collected at 10 and 20 day after treatment. Expression of the transformation is phenomenal concentration of blood cells around the liver pancreas and some changes in the structure of the hepatopancreas tube. When exposed at higher concentrations (80% or higher value of LC), the majority of experimental shrimp died within 10 days after exposure.